Performance on the single-legged step down and running mechanics - Schreiber, C.; Becker, J. (Journal of Athletic Training, 2020)
Context: Previous authors have shown associations between kinematics on the single-legged step down (SLSD) and running mechanics. Therefore, the SLSD may be a useful tool for identifying runners with poor running mechanics when 2- or 3-dimensional gait analysis is not available. However, the associations between SLSD performance and running kinetics, as well as the influences of sex and muscle strength on these relationships, remain unclear. Objective: To evaluate whether kinematics on the SLSD predict kinematics and kinetics while running and whether the relationships differ between men and women and are mediated by muscle strength. Design: Cross-sectional study. Setting: Biomechanics research laboratory. Patients or Other Participants: Fifty highly trained runners (25 men, 25 women; age = 27.8 ± 9.2 years, height = 1.69 ± 0.26 m, mass = 66.3 ± 15.0 kg, running distance = 45.2 ± 19.1 mile/wk [72.32 ± 30.56 km/wk]). Main Outcome Measure(s): Relationships between kinematics on the SLSD and kinematics and kinetics during running were evaluated. We also assessed whether muscle strength moderated these relationships. Results: For men, linear regression revealed that peak hip adduction (R2 = 0.306, P = .012), internal rotation (R2 = 0.439, P = .002), knee valgus (R2 = 0.544, P = .001), and rearfoot eversion (R2 = 0.274, P = .008) on the SLSD were strongly predictive of kinematics during running. In women, only peak hip internal rotation (R2 = 0.573, P = .001), knee valgus (R2 = 0.442, P = .001), and rearfoot eversion (R2 = 0.384, P = .012) predicted running kinematics. In women, total medial collapse on the SLSD predicted peak hip-adductor moment (R2 = 0.364, P = .001) during running. None of the relationships were moderated by muscle strength in either men or women. Conclusions: Kinematics during the SLSD predicted kinematics while running in both men and women but only predicted kinetics while running in women. Given that none of the relationships between SLSD performance and running mechanics were moderated by muscle strength, clinicians should assess movement quality and strength independently.